A five-year follow‐up study of the general public awareness and perception of epilepsy in Croatia - Bagić, Dragan (Array, 2012)
Public reception of epilepsy in Croatia was re-assessed in 2009, 5 years after an initial survey, by interviewing 1000 randomly selected adults. Ninety-two percent (−5.0%) of the respondents had heard about epilepsy, 47% (−7.9%) knew someone with epilepsy, and 38.6% (−6.0%) had witnessed a seizure. Interviewees were quite ready to accept a person with epilepsy. Almost 8% (+1.1%) would object if their child played with a child with epilepsy, and 77.8% (+1.8%) believed that a child with epilepsy could succeed as well as a child without epilepsy. Although 45.9% (−6.6%) would approach a person having a seizure and help, 36.1% (+3.0%) would also call “911.” Citizens of Croatia re-declared a high tolerance toward people with epilepsy and positive attitude toward children with epilepsy. Experiential factors remained strong predictors of more positive attitudes. A more prominent role of patients and implementation of social marketing in addressing a large persisting degree of prejudice and stigmatization worldwide are warranted.